2015
DOI: 10.1002/pon.3829
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and quality of life in lung cancer: the role of health‐related stigma, illness appraisals and social constraints

Abstract: ObjectiveHealth‐related stigma is associated with negative psychological and quality of life outcomes in lung cancer patients. This study describes the impact of stigma on lung cancer patients' psychological distress and quality of life and explores the role of social constraints and illness appraisal as mediators of effect.MethodsA self‐administered cross‐sectional survey examined psychological distress and quality of life in 151 people (59% response rate) diagnosed with lung cancer from Queensland and New So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
111
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 38 publications
9
111
2
Order By: Relevance
“…2, 811 Greater distress and reduced QoL in lung cancer patients have been associated with lower self-efficacy or confidence in their ability to manage symptoms and greater social constraints (e.g., avoidance, criticism) on cancer-related disclosure. 12, 13 …”
Section: Introductionmentioning
confidence: 99%
“…2, 811 Greater distress and reduced QoL in lung cancer patients have been associated with lower self-efficacy or confidence in their ability to manage symptoms and greater social constraints (e.g., avoidance, criticism) on cancer-related disclosure. 12, 13 …”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, the quality of life of cancer patients is closely linked to cancer stigma; that is, the worse the quality of life, the greater the cancer stigma the patient presents [8,12,14]. The QLQ-C30 seems to be an adequate instrument to verify the concurrent validity of the KCSS because the degree of perceived cancer stigma suffered by 124 www.jkan.or.kr role, emotional, cognitive, and social aspects), and symptom (13 items assessing fatigue, nausea and vomiting, pain, dyspnea, insomnia, appetite loss, constipation, diarrhea, and financial problems).…”
Section: (Eortc Qlq-c30)mentioning
confidence: 99%
“…To evaluate the known-group validity of the KCSS, we used Korean version of the psychological symptom inventory (PSI) developed by the National Cancer Center [3] which measure psychological distress that was proposed as closely related variables to the cancer stigma in previous studies [4,5,8,11,14], and use of the instrument was confirmed through an e-mail. The PSI assessed the current distress levels of three symptoms and interference with daily activities (insomnia, anxiety, and depression).…”
Section: ) Psychological Distress: Psychological Symptom Inventory (mentioning
confidence: 99%
See 1 more Smart Citation
“…Research from North America has found stigma and shame about lung cancer, social isolation and smoking-related stigma to be associated with delay in seeking medical help by lung cancer patients [18, 19]. Other researchers have found that lung cancer patients who have more internalised shame about their cancer are more likely to conceal their diagnosis from their social network [20] and that the negative effects of stigma and shame on lung cancer patients distress and quality of life were mediated by cancer threat and social constraints [21]. Hence, stigma influences the patient experience of lung cancer and although objective studies of actual discrimination in cancer treatment are not evident, stigma seems likely to influence the care pathway.…”
Section: Introductionmentioning
confidence: 99%